Haida totem poles and wooden structure, village of Howkan, Long Island, Alaska, ca. 1923. - Thwaites, John E.
Two Kaijani totem poles sit in front of a wooden structure. The Kaijani are a subtribe of the Haida Indians. Caption on image: Thwaites 5859. Indian totems at a deserted village, Alaska Note from unidentified source: Commemorative poles from Howkan. On left, pole symbolizing a long tale of a man (sitting between the ears of the bear at the base of the pole) who turned into a sea monster (above him) and who was betrayed by his mother-in-law (the small figure with headdress and ring rattles). On right, a mortuary pole with blackfish on top and bear at the base. These poles belonged to the same lineage. They were copied for the Hydaburg totem park. In Garfield Volume 1, leaf 35